Knee joint endoprosthetics for rheumatoid arthritis - Xo’janazarov Ilxom Eshqulovich; Axmedov Xalmurad Sa’dullayevich; Anorboyev Ma’ruf Xolbo’ta o’g’li (Zien Journals, 2024)
Determination of the immediate outcomes of disease course, preparation for surgery and treatment during knee joint endoprosthetics of patients with rheumatoid arthritis.
Keywords: Knee joint; endoprosthetics